2022
DOI: 10.1093/ofid/ofac240
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in Hematologic Malignancy Patients With Fever and Neutropenia: Are Empirical Antibiotic Therapies in the United States Still Effective?

Abstract: Background Rising antimicrobial resistance rates may impact the efficacy of empirical antibiotic treatment for febrile neutropenia in high-risk cancer patients. Lacking contemporary data about the epidemiology, antibiotic resistance patterns, and clinical outcomes from bloodstream infections (BSI) in U.S. cancer patients, it is unclear if current guidelines remain relevant. Methods In a cross-sectional study, fourteen U.S. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…as most infections remain susceptible to the anti-pseudomonal beta-lactams. 28,29 Access to rapid diagnostic platforms that identify pathogen and resistance markers allow clinicians to respond earlier and transition to these agents when necessary. Local antibiograms play a critical role in determining the role of these therapeutics in the management of this vulnerable population.…”
Section: F I G U R E 3 Commonly Used Antimicrobials During Leukemia C...mentioning
confidence: 99%
See 1 more Smart Citation
“…as most infections remain susceptible to the anti-pseudomonal beta-lactams. 28,29 Access to rapid diagnostic platforms that identify pathogen and resistance markers allow clinicians to respond earlier and transition to these agents when necessary. Local antibiograms play a critical role in determining the role of these therapeutics in the management of this vulnerable population.…”
Section: F I G U R E 3 Commonly Used Antimicrobials During Leukemia C...mentioning
confidence: 99%
“…Newer broad spectrum agents (e.g., ceftazidime‐avibactam, cefiderocol), designed to target carbapenem resistant Enterobacterales, have largely replaced more toxic agents like the polymyxins. While it may be enticing to consider these agents as first line in the immunocompromised patient, they have not been shown to be better empirically, as most infections remain susceptible to the anti‐pseudomonal beta‐lactams 28,29 . Access to rapid diagnostic platforms that identify pathogen and resistance markers allow clinicians to respond earlier and transition to these agents when necessary.…”
Section: Antibacterialsmentioning
confidence: 99%
“…Enterobacterales comprise the majority of Gram-negative BSIs during chemotherapy-induced neutropenia. [11][12][13] Unfortunately, FQ resistance has become increasingly common in Enterobacterales in the United States. 14 In a recent multicenter study, 22% of urinary Escherichia coli isolates from ambulatory patients were FQ-R and 28% of isolates from hospitalized patients were FQ-R. 15 A high prevalence of FQ-R E has also been observed among patients with hematologic malignancies and HCT recipients.…”
Section: Fluoroquinolone-resistant Enterobacterales (Fq-r E)mentioning
confidence: 99%
“…14 In a recent multicenter study, 22% of urinary Escherichia coli isolates from ambulatory patients were FQ-R and 28% of isolates from hospitalized patients were FQ-R. 15 A high prevalence of FQ-R E has also been observed among patients with hematologic malignancies and HCT recipients. A multicenter US study of BSIs during fever and neutropenia found that 53% of Enterobacterales bloodstream isolates were FQ-R. 13 FQ-R E are also common in other countries. A multicenter Italian study of 342 BSIs due to E. coli in patients with hematologic malignancies found that 70% of isolates were resistant to FQs.…”
Section: Fluoroquinolone-resistant Enterobacterales (Fq-r E)mentioning
confidence: 99%
See 1 more Smart Citation